2017
DOI: 10.1136/postgradmedj-2017-135129
|View full text |Cite
|
Sign up to set email alerts
|

Study of fall risk-increasing drugs in elderly patients before and after a bone fracture

Abstract: The use of FRIDs among patients with a fall-related fracture is very high. This use rises 1 month after the fracture, significantly in the case of hypnotics and antidepressants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 22 publications
1
26
0
Order By: Relevance
“…However, the estimated 41% prevalence of suspected medication-related falls suggests that medications are a major risk factor. We have not identified other studies estimating the prevalence of medication-related falls in hip fracture patients, and we were expecting a higher occurrence of suspected medication-related falls due to the frequent use of FRIDs in hip fracture patients [10,11]. Medications can be considered modifiable risk factors, and we identified an overlap between medications found to contribute to the fall episode and medications identified as PIMs in the majority of the patients with a suspected medicationrelated fall.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…However, the estimated 41% prevalence of suspected medication-related falls suggests that medications are a major risk factor. We have not identified other studies estimating the prevalence of medication-related falls in hip fracture patients, and we were expecting a higher occurrence of suspected medication-related falls due to the frequent use of FRIDs in hip fracture patients [10,11]. Medications can be considered modifiable risk factors, and we identified an overlap between medications found to contribute to the fall episode and medications identified as PIMs in the majority of the patients with a suspected medicationrelated fall.…”
Section: Discussionmentioning
confidence: 75%
“…The association between falls and the use of cardiovascular medications, including antihypertensives and antiarrhythmics, does not seem quite as consistent [6]. However, in clinical practice, cardiovascular medications are often regarded as FRIDs, [9,10] as their adverse effects can directly or indirectly cause dizziness, hypotension and orthostatic hypotension. Several reports have shown that more than 90% of elderly people experiencing a fall or a hip fracture are taking FRIDs [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the observational studies categorized according to the strength of the study design to capture changes in FRID use after a fall‐related injury are provided in Table . In the first group of studies, FRID use was measured at admission, as well as time points following discharge (1 month and 6 months), and no change in FRID use was found. In the second group of studies that compared FRID use at admission and discharge, one study found no change in FRID use, whereas one found a reduction in FRID use .…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of suspected medication-related falls is about 41% [ 555 ] to 49% [ 556 ]. Increased risk of falls was documented in users of anxiolytics/hypnotics, opioids, sedatives, antihypertensives (especially alpha-blockers), antidepressants, antiparkinsonian medications, antiepileptics and antiarrhythmics [ 557 , 558 , 559 , 560 , 561 , 562 , 563 , 564 , 565 , 566 , 567 , 568 , 569 , 570 , 571 , 572 , 573 , 574 , 575 , 576 , 577 , 578 , 579 , 580 , 581 , 582 , 583 ]; polypharmacy is strongly associated with injurious falls and fractures [ 574 , 582 , 584 , 585 , 586 , 587 , 588 ].…”
Section: Hpi-associated Chronic Extra-gastroduodenal Diseases Medmentioning
confidence: 99%